Teaching World War I: An exploratory study of representations of the Great War in contemporary African textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
World War I (WW1) is widely recognised as an event of critical significance and far-reaching consequences, a violent episode of unprecedented magnitude which affected millions of lives and which brought lasting change to the world in which we live. One hundred years after the outbreak of this global war, successive younger generations across the globe have been taught about this watershed event in world history. This paper seeks to fill a notable gap in extant research on WW1 by exploring the ways in which the history of this war is taught to Africa’s younger generations through the findings of an exploratory study on representations of the Great War in recent African school textbooks. The study draws on an analysis of over 30 history and social studies textbooks from 15 different countries to investigate the core questions around which lessons on WW1 are designed across the continent, and the specific knowledge conveyed and emphasised in the answers provided to these questions. The article demonstrates efforts, found across African textbooks, to reclaim and re-centre local historical agency, experiences, and views related to WW1, while also pointing to the possibility to better valorise this part of national, African and world heritage to learn meaningful lessons for the present and the future.
Keywords: World War I; Textbooks; African history; Colonialism; Representations; Historical consciousness; African consciousness